Γ-ray Irradiation-Induced Chemical and Structural Changes in CVD Monolayer MoS2. (14th September 2020) - Singh, Aditya; Singh, R.
Abstract : Two dimensional (2D) materials are the ideal choice for highly efficient, lightweight, low power consumption nanoelectronics in space science applications. Therefore, investigation of radiation hardness of 2D-materials is of great interest. Herein, we report the effect of gamma irradiation on chemical vapor deposition (CVD) synthesized crystalline monolayer (1 L) molybdenum disulfide (MoS2 ) flakes on the sapphire substrate at various doses, viz., 1–1000 kGy. We estimated that the temperature of MoS2 increases by 1.3 °C per kGy of gamma-ray dose. It was observed that up to 130 kGy (∼195 °C), gamma exposure has no significant impact on the morphology and chemical properties of MoS2 . However, X-ray photoelectron spectroscopy (XPS) shows that from 275 kGy (∼385 °C), MoS2 starts converting into MoOx . Raman spectroscopy shows that at low gamma doses, the crystallinity of MoS2 increases while at higher doses, a traceable amount of MoS2 starts converting into amorphous MoS3 . Our findings show that both E 1 2g and A1g Raman mode of MoS2 blue shift as gamma dose increases owing to the combined effect of sulfur vacancies creation and strain caused by thermal expansion of MoS2 .